A content analysis on the impression management of top filipino beauty youtubers in their beauty videos - Angeles, Alexandra Leonora Jean S. (2019)
There is a growing popularity of YouTube (Top 250 YouTubers in Philippines Sorted by SB rank, 2018), the YouTuber career (Kharmis, Ang & Welling, 2016), and beauty videos (Kantar TNS, 2017 as cited in YouTube: the Philippine most popular online platform, 2018) in the Philippines. Thus, this thesis looked into how and what the YouTubers communicate that have made YouTube, themselves, and their interests popular. Specifically, the impression management of the top Filipino beauty YouTubers in their study videos were studied through a quantitative-qualitative content analysis and by employing Goffman?s Impression Management Theory. Findings show that the top Filipino beauty YouTubers perform the Integratiation Image Management (IM) Tactic and brand for their own economic gains. Results on the commonly performed self-presentation behaviors, image management tactics, and personality traits may be useful for other YouTubers and YouTube users to know and understand the behaviors, expressions, and impressions that can be shown in order to gather and maintain an audience and market on YouTube in the Philippines